The significance of Mindanao conflict in the news and agenda of Mindanao Daily Mirror and Mindanao Times - Abian, Gian Alexis I.
Local newspapers are assumed to have an advantage in gathering news closer to where they are stationed compared to their national broadsheet counterparts. The study focused on the two(2) Davao-based community newspapers namely, Mindanao Daily Mirror and Mindanao Times and how they regard the Mindanao conflict in their publications. The number of stories published in the month of October 2008 was narrowed down until only the relevant articles were identified. Only straight news, regular columns, special columns, editorials and letters to the editor were considered. The screening yielded 53 articles from Mindanao Daily Mirror and 39 articles from Mindanao Times. The studies main objective was to identify the agenda of both newspapers, using the Agenda-setting theory. The analysis was also based on the first level of agenda-setting theory, which excludes framing, focusing only on through what elements are the newspaper companies able to set their agenda on the Mindanao conflict. The study revealed that both newspaper used all elements, I. e. prominence, sources and actor, treatment, and tone, in setting the agenda of the Mindanao conflict. Mindanao Daily Mirror however appeared to give more prominence to the Mindanao conflict more than Mindanao Times, in terms of frequency and page prominence. The former also appeared to publish more articles other than the straight news type, setting the agenda through opinion articles such as the columns, editorial, and letter to the editor. Moreover, both appeared to publish articles which are substance-based more than production-based articles. The study was able to conclude that both newspapers regard the Mindanao conflict as highly significant and sets the agenda of the issue by using more substance-based articles in greater frequency and prominence.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts